Nanopore-Templated Silver Nanoparticle Arrays Photopolymerized in Zero-Mode Waveguides - Han, Donghoon; Crouch, Garrison M.; Chao, Zhongmou; Fullerton-Shirey, Susan K.; Go, David B.; Bohn, Paul W. (Frontiers in Chemistry, 2019)
In situ fabrication of nanostructures within a solid-polymer electrolyte confined to subwavelength-diameter nanoapertures is a promising approach for producing nanomaterials for nanophotonic and chemical sensing applications. The solid-polymer electrolyte can be patterned by lithographic photopolymerization of poly(ethylene glycol) diacrylate (PEGDA)-based silver cation (Ag+)-containing polyelectrolyte. Here, we present a new method for fabricating nanopore-templated Ag nanoparticle (AgNP) arrays by in situ photopolymerization using a zero-mode waveguide (ZMW) array to simultaneously template embedded AgNPs and control the spatial distribution of the optical field used for photopolymerization. The approach starts with an array of nanopore-confined recessed Ag ring electrodes fabricated by sequential layer-by-layer deposition and focused ion beam milling. These structures have an optically transparent bottom, allowing access of the optical radiation to the attoliter-volume ZMW region to photopolymerize a PEGDA monomer solution containing AgNPs and Ag+. The electric field intensity distribution is calculated for various ZMW optical cladding layer thicknesses using finite-element simulations, closely following the light-blocking efficiency of the optical cladding layer. The fidelity of the polyelectrolyte nanopillar pattern was optimized with respect to experimental conditions, including the presence or absence of Ag+ and AgNPs and the concentrations of PEGDA and Ag+. The self-templated approach for photopatterning high-resolution photolabile polyelectrolyte nanostructures directly within a ZMW array could lead to a new class of metamaterials formed by embedding metal nanoparticles within a dielectric in a well-defined spatial array.